Scale up sediment microbial fuel cell for powering Led lighting - Prasad, Jeetendra; Tripathi, Ramesh Kumar (Center of Biomass & Renewable Energy, Diponegoro University, 2018)
Sediment microbial fuel cells (SMFCs) are expected to be utilized as a sustainable power source for remote environmental observing 30 day’s investigations of experiment to understand the long-term performance of SMFCs. The point of this investigation is to increase power generation, 8 individual sediment microbial fuel cells is stacked together either in series or in hybrid connection. Two combinations, of the hybrid connection, are proving to be the more effective one, step-up both the voltage and current of the framework, mutually. Polarization curve tests are done for series and hybrid connected sediment microbial fuel cell. The maximum study state voltage and current are obtained 8.150V and 435.25µA from series and 4.078V and 870.75µA hybrid connected SMFC. This study suggests that power of SMFC scale-up by connecting series and hybrid for practical use of the device.Article History: Received : September 26th 2017; Received: December 24th 2017; Accepted: January 4th 2018; Available onlineHow to Cite This Article: Prasad, J and Tripathi, R.K. (2018) Scale Up Sediment Microbial Fuel Cell For Powering Led Lighting. International Journal of Renewable Energy Development, 7(1), 53-58.https://doi.org/10.14710/ijred.7.1.53-58